Current sources of lead exposure and their relative contributions to the blood lead levels in the general adult population of Northern France: The IMEPOGE Study, 2008–2010. Issue 6 (18th March 2016) - Tagne-Fotso, Romuald; Leroyer, Ariane; Howsam, Mike; Dehon, Betty; Richeval, Camille; Nisse, Catherine
ABSTRACT: There is justification for limiting lead (Pb) exposure as much as possible, given its impact on health at low concentrations. Consequently, the aim of this study was to measure blood lead levels (BLL) and examine exposure factors related to BLL variations in the general adult population of northern France, a current and past industrial area. Two thousand inhabitants of northern France, aged between 20 and 59 years, were recruited using the quota method with caution. Blood lead levels were quantified by inductively coupled plasma–mass spectroscopy (ICP-MS), and variation factors were studied separately in men and women using multivariate stepwise linear and logistic regression models. The geometric mean of the BLL was 18.8 μg/L (95% confidence interval [CI]: 18.3–19.3). Occupational factors affected BLL only in men and represented 14% of total explained variance of BLL. External occupational factors significantly increasing mean levels of BLL were tobacco, consumption of some beverages (wine, coffee, tea, and/or tap water), raw vegetables, housing characteristics (built prior to 1948, Pb piping in the home) and do-it-yourself or leisure activities (paint stripping or rifle shooting). Consumption habits accounted together for 25% and 18% of the total explained variance, respectively, in men and women. Industrial environment did not significantly contribute to BLL variations. Blood lead levels observed in the general population of this industrial part of France did not appear to be excessively elevated compared to values found internationally. Nonetheless, these BLL remain a public health issue in regard to nonthreshold toxicity attributed to Pb.